The History and Doctrines of the Maturidiyah School of Though - Restu R; Indo Santalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research discusses the Maturidiyah school of thought (its history and teachings). The objectives of this study are: to understand the history of the birth of the Maturidiyah school, to understand the teachings of the Maturidiyah school, to identify the theological group of Maturidiyah, and to understand the doctrines of Maturidiyah theology. The author employs a qualitative research method. To collect data, the author utilizes literature by analyzing various references relevant to the topic discussed, both in Indonesian and foreign languages. In addition, the research sources also include primary data. The result of the research is that his full name is Imam Abu Mansur Muhammad bin Muhammad bin Mahmu Al Maturidi. He is called Al Maturidi based on the name of the small village where he was born, namely Maturid, which is located around Samarkand. Al Maturidi and the followers of the Maturidiah school believe in the existence of objective evil related to an action, and that the human mind is capable of judging the goodness or badness of an act. They seem to categorize actions into three groups: the category whose goodness cannot be fully understood through reason, the category whose evil cannot be fully understood by reason, and another category whose good and bad are not clear to reason. For this last category, goodness and badness can only be understood through sharia (religious law). The al-Maturidiyah school includes several points: First, the obligation to recognize God, where according to al-Maturidi, reason has the ability to inform the necessity of knowing God. Second, concerning goodness and badness, al-Maturidi (and also followers of Maturidiyah) acknowledges the existence of objective evil inherent in the act itself, and that reason can understand the goodness and badness of some actions.